The ozone layer, located in the stratosphere, plays a crucial role in protecting - Mishra, Meghana (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 11 No 3&4 (2024): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2024)
The ozone layer, located in the stratosphere, plays a crucial role in protecting life on Earth by absorbing the majority of the sun's harmful ultraviolet (UV) radiation. However, human activities, particularly the release of ozone-depleting substances (ODS) such as chlorofluorocarbons (CFCs), halons, and other chemicals, have led to significant depletion of this vital layer. This review examines the multifaceted causes and dire consequences of ozone layer depletion, including its impact on human health, ecosystems, and climate change. The article highlights the success of international efforts, particularly the Montreal Protocol, in mitigating these effects and facilitating the recovery of the ozone layer. However, challenges remain, such as the illegal production of ODS and the emergence of new substances that threaten its stability. By emphasizing the importance of ongoing research, public awareness, and technological innovation, this review aims to underscore the need for sustained global cooperation to protect this essential component of the Earth’s atmosphere and ensure the well-being of future generations.